A novel hybrid radio over fiber visible light communication system combining 5G mmWave and coarse wavelength division multiplex grid - Muhammad Towfiqur Rahman; Rajendran Parthiban; Masud Bakau (Institute of Advanced Engineering and Science, 2023)
Visible light communication(VLC)has gained attention for enabling gigabitdata transmission over a short-range. Inradio over fiber (RoF), modulatedradio frequency (RF) is carried over optical fiber. Millimeter-wave (mmW)range also offers a vast amount of spectrum and enables integration with RoF.We propose a novel hybrid network using mmWave based RoF backhaulandcoarse wavelength division multiplexed(CWDM)-VLC for indoorcommunication. Three different optical tones were introduced to produce thedesired mmW signal using optical heterodyning with one of them carryingmodulated data and the other two carrying unmodulated data. Opticalsideband signal with the carrier(OSSB+C) is used for uplink communication.Modulated mmWave signal is used for VLC downlink to drive a multi-colorCWDM system. The performance of the VLC downlink is measured usingdifferent optical filters such as Bessel, Trapezoidal, Gaussian, and FabryPerot. A maximum data rate of 2.64 Gb/s and 6.58 Gb/s were achieved with10 and 20channelsoff the shelf LEDs with 16quadrature amplitudemodulation (QAM) with reasonable BER for downlink VLC communication.The uplink communication was carried out using mmW with 2.5 Gb/s datarate usingon-off keying(OOK)modulation and the data from thiscommunication down converted atcentral office(CO) through RoF backhaul.